Implementasi CCTV berbasis NVR untuk Meningkatkan keamanan di Pesantren Markaz Hadits Legok: Implementation of NVR based CCTV to Improve Security at The Markaz Hadits Legok Islamic Boarding School - Rosiana, Elfirza; Abdurahman, Abdurahman; Gunastuti, Dwi Anie; Maisari, Linda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Cases of bullying and theft continue to occur frequently within Islamic boarding schools, including at the Markaz Hadits Legok boarding school, which has led to a decline in the sense of safety and comfort during the learning process. Consequently, a system is needed to minimize security breaches and evaluate the behavior of boarding school residents, thereby facilitating appropriate guidance and mentoring. The implementation of a Closed-Circuit Television (CCTV) system based on a Network Video Recorder (NVR) is a solution that can enhance security, comfort, and discipline in the boarding school environment. The stages of this community service project began with field observations to ensure the proposed solution aligns with the partner’s needs. This was followed by a system needs analysis, CCTV installation, system configuration, system testing, and evaluation. As a result, CCTV cameras were installed at six strategic locations that effectively cover nearly all areas. Data is displayed in real time at the monitoring center, securely stored, and can be retrieved as needed. Additionally, training was provided to selected users. The training covered how to address simple malfunctions, access procedures, and how to retrieve recordings.